Pecutan as Myth in Abdul Muluk’s Traditional Theatre Perfomance - Wulandari, Iis; Syafutri, Husni Dwi (Jurusan Sejarah, Seni, dan Arkeologi, FKIP, Universitas Jambi, 2024)
Pecutan is part of the property used in the Abdul Muluk Tradition Theater performance. The Pecutan are made of wood or bamboo, the length of which is adjusted as desired. Abdul Muluk is a traditional theater that developed around the 1930s in Jambi Province, Indonesia. It tells the story of King Abdul Muluk who is wise in leading his kingdom. The story of Abdul Muluk comes from the poem Sultan Abdul Muluk written by King Ali Haji during the Malay Empire. This research aims to analyze Pecutan as a myth in Abdul Muluk's traditional theater performance. This research uses a qualitative method with an ethnographic approach that aims to understand the perspectives of actors and audiences of Abdul Muluk's traditional theater regarding Pecutan. Data was obtained through observation of video documentation of Abdul Muluk's traditional theater performances which focused on the myth and the use of Pecutan. Data was also obtained through in-depth interviews with actors, audiences, and theater artists in Jambi. Data analysis used the Miles and Huberman Model through data reduction, data presentation, and conclusion drawing. The research results of the Pecutan myth show the meaning of masculinity seen in the King Figure in the story—cultural representation of the people of Jambi Province regarding Pecutan as a marker of an order. Pecutan has an important role in the performance, namely as a marker for the entry of music, the start of dialog, and the transition of dialog. These findings provide a deep understanding of how Pecutan can reflect the culture of the people of Jambi Province only through Abdul Muluk's traditional theater performances. With a better understanding of this, the government, culturists, artists, and traditional actors can maintain and preserve Pecutan, which will become a valuable art asset in the future.